Studi Perencanaan Saluran Samping Ruas Jalan Bayangkara Tanah Grogot Kabupaten Pasir - Rosehan Anwar (Universitas Lambung Mangkurat, 2007)
Evaluation from the existing drainage infrastructure, there is indication that level of the need has exceeded level of service. If we evaluated the problem in general, hence arising problem are the presence of ponds especially as result at rain water at low land district, and drag of current as result of by rain intensity that is blow far again. Therefore the planning of new drainage systems is important supporting development of region.Analysis method applied are hydrology method and hydraulic method.Result of planning drainage is got by side passage which form of trapezium, basic breadt h=0,55m, maximum water dept= 0,35m, dip of passage basic=0,934%, passage height=4,2m, passage peak with = 0,75m, side passage with form of rectangular b=2d, basic breadth=0,33m, maximum water depth=0,66m, did of passage basic=1,33%, passage height=5,75m,gorong-gorong(cloced channel), diameter (D) =0,57m, water height (d) = 0,46m, dip of passage basic (i) = 0,5%.